The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1158/1078-0432.ccr-10-2621
|View full text |Cite
|
Sign up to set email alerts
|

Combination mTOR and IGF-1R Inhibition: Phase I Trial of Everolimus and Figitumumab in Patients with Advanced Sarcomas and Other Solid Tumors

Abstract: Purpose: Preclinical models demonstrate synergistic antitumor activity with combination blockade of mTOR and IGF-1R signaling. We aimed to determine the safety, tolerability, and recommended phase II dose (RP2D) of the combination of figitumumab, a fully human IgG 2 anti-insulin-like growth factor-1 receptor (IGF-1R) monoclonal antibody (Pfizer) and the mTOR inhibitor, everolimus (Novartis). Pharmacokinetics and preliminary antitumor effects of the combination were evaluated.Experimental Design: Phase I trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
103
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(113 citation statements)
references
References 28 publications
3
103
0
7
Order By: Relevance
“…Few patients with advanced ACCs who received everolimus, as salvage treatment, did not receive any major benefit (Fraenkel et al 2013). Few ACC patients have been treated in registered clinical trials (Gangadhar et al 2011, Quek et al 2011, Naing et al 2013. These studies failed to prove the hoped efficacy of these compounds, and they also had limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few patients with advanced ACCs who received everolimus, as salvage treatment, did not receive any major benefit (Fraenkel et al 2013). Few ACC patients have been treated in registered clinical trials (Gangadhar et al 2011, Quek et al 2011, Naing et al 2013. These studies failed to prove the hoped efficacy of these compounds, and they also had limitations.…”
Section: Discussionmentioning
confidence: 99%
“…As mitotane can interfere with the metabolism of other drugs including mTOR inhibitors, it became necessary to determine mitotane levels in these patients. However, these early clinical experiences suggest that a subset of patients could benefit (more than 6 months of tumor stabilization) from combined treatment including mTOR inhibitors and IGF1R antagonists (Quek et al 2011, Naing et al 2013. In a previous study, we had demonstrated that, in H295 ACC cells, IGFs can activate mechanisms of escape from mTOR inhibitors, which could be responsible for a reduced sensitivity to the treatment with these drugs (De Martino et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A recent phase I combination study of figitumumab and the mTOR inhibitor, everolimus, in patients with advanced sarcomas and other solid tumors indicated that the combination was well tolerated with no unexpected toxicities. Stable disease was observed in the majority of patients and the combination also yielded a partial response in one patient with malignant solitary fibrous tumor (42). Furthermore, a phase I trial evaluating the humanized anti-IGF1R monoclonal antibody, dalotuzumab, combined with the mTOR inhibitor, ridaforolimus, demonstrated antitumor activity in patients with estrogen receptor-positive metastatic breast cancer (43).…”
Section: Discussionmentioning
confidence: 99%
“…These findings raised the question whether the combination of IGF-1R and mTOR inhibitors in patients with NSCLC might be more effective. Several preclinical experiments had demonstrated synergistic antitumor activity with combination blockade of mTOR and IGF-1R signaling (Quek et al, 2011).…”
Section: Discussionmentioning
confidence: 99%